Register Now!

Search Skwirk

We know that an is for n = 0, 1, 2, 3, ...

We shall now find out what an is when n is negative.

We know that    and we used his to find a0 (we also implicitly used this to find a1).

We shall now use this to find an when n is negative.













We could also have derived this in other ways.

One way is by saying that



     a-n = (a-1)n

Another way is by noting that

     an x a-n = an - n

                  = a0

                  = 1

Thus a-n x a-n = 1


Pop Quiz

The more you learn - the more you earn!
What are points?Earn up to points by getting 100% in this pop quiz!

Question 1/5

1. Write ( a)-2 x (3b-3)3 as a fraction


No thanks. Remind me again later.